Epistemologi Hadis Sufistik Syekh Ihsan Jampes dan Relevansinya Terhadap Problematika Krisis Etika Sosial Perkotaan - Muhammad Arwani Rofii; Siti Fatimatuz Zahroh (Al-Mu'tabar, 2026)
Urban social problems in the modern era are characterized by the intensification of identity crises, symbolic competition culture, and tendencies toward social narcissism that trigger alienation and weaken the collective ethics of urban society. These phenomena indicate that urban social problems do not merely stem from structural and economic aspects, but are also rooted in the epistemological and spiritual problems of human beings. This article aims to examine the epistemology of Sufistic hadith in Shaykh Ihsan Jampes’ Kitab Manāhij al-Imdād and to analyze its relevance to urban social problems. This study employs a qualitative method based on textual analysis with an integrative Islamic epistemological approach emphasizing bayānī and ‘irfānī reasoning. The analysis focuses on how Shaykh Ihsan Jampes understands hadiths concerning arrogance (kibr) and self-admiration (‘ujub) as inner spiritual diseases that disrupt the formation of ethical consciousness and human identity. The findings reveal that Shaykh Ihsan Jampes’ Sufistic hadith epistemology positions kibr and ‘ujub not merely as individual moral violations, but as epistemological disturbances that damage human social and spiritual relations. This perspective has significant relevance in understanding urban social problems, particularly within the context of performative culture, social egoism, and community fragmentation. This article affirms that the integration of Sufistic hadith epistemology can enrich urban management discourse through the strengthening of social ethics, identity resilience, and urban human development oriented toward spiritual values.